Bone-conduction hearing and seismic sensitivity of the late permian anomodont Kawingasaurus fossilis - Laaß, Michael (Journal of morphology, 2015)
An investigation of the internal cranial anatomy of the anomodont Kawingasaurus from the Upper Permian Usili Formation in Tanzania by means of neutron tomography revealed an unusual inner and middle ear anatomy such as extraordinarily inflated vestibules, lateroventrally orientated stapes with large footplates, and a small angle between the planes of the anterior and lateral semicircular canals. The vestibule has a volume, which is about 25 times larger than the human vestibule, although Kawingasaurus has only a skull length of approximately 40 mm...